Pengaruh Tingkat Pendidikan Dan Perhatian Orang Tua Terhadap Motivasi Belajar Matematika Pada Siswa Kelas IV SD 10 Petarukan Pemalang Tahun Ajaran 2015/2016 - Kartika, Septiani Dian, Drs. Suwarno, SH, M.Pd (2016)
The purpose of this study is to: (1) Determine the influence of parental education on motivation to learn math at the fourth grade students of SD Negeri 10 Petarukan Pemalang in the academic year 2015/2016, (2) Determine the influence of parents' attention to the motivation to learn mathematics fourth grade students of SD Negeri 10 Petarukan Pemalang in the academic year 2015/2016, (3) Determine the influence of education level and parental supervision of students' motivation to learn mathematics in fourth grade N 10 Petarukan Pemalang in the academic year 2015/2016. This research is descriptive quantitative research to draw conclusions through statistical analysis. The population in this study were all students in fourth grade N 10 Petarukan Pemalang totaling 36 students. The sample in this study used a population sample. Data collection techniques in this study was a questionnaire and documentation. Data analysis technique used is multiple linear regression analysis, t test, F test, the coefficient of determination and the relative contribution and effective contribution that preceded the prerequisite test analysis is the normality test and linearity test. Based on the analysis of multiple linear regression equation: Y = 30.532 + 2.632 X1 + 0.522 X2. The results of the data analysis significance level of 5% was obtained: (1) The level of parental education and significant positive effect on motivation to learn mathematics. This is based on test results t is known that tcount> ttable, namely 4.293> 2.032 and the significance value <0.05 is 0.000 with the relative contribution of 48.1% and the effective contribution of 28.7%. (2) Attention parents and significant positive effect on motivation to learn mathematics. This is based on test results t is known that tcount> ttable, namely 4.501> 2.032 and the significance value <0.05 is 0.000 with the relative contribution of 51.9% and the effective contribution of 31.1%. (3) The level of education and parental concern and significant positive effect on motivation to learn mathematics. This is based on test F known that Fhitung> Ftable is 24,500> 3.23 with a significance value <0.05 is 0.000. From the test results of determination (R2) obtained the results for 0598 show that the level of education and parental supervision of their motivation to learn mathematics is 59.8%, while the remaining 40.2% is influenced by other factors.